Cooperative Games and Art Therapy for reducing the Tantrum Rating Scale in Preschool Children at Ulul Albab Kindergarten - Eli Rahmawati; Indasah Indasah; Agustin Widyowati (Universitas Tribhuwana Tunggadewi, 2026)
Temper tantrums are a common behavioral challenge during early childhood development. Managing this behavior is important to support children’s emotional and social development. One approach that has been explored to address this issue is the use of cooperative games, which emphasize collaboration and shared goals among children. This study examined the effect of cooperative games and art therapy on temper tantrum reactions in preschool-aged children at Ulul Albab Kindergarten, Jombang. Through a quasi-experimental method with a pretest-posttest control group design, Data were collected from 78 children as a population. The sampling technique used Stratified Random sampling obtained 69 research samples by applying the proportional strata formula. The research instrument used the Temper Tantrum Rating Scale. The research sample was divided into 3 groups, namely the cooperative game play intervention group, the art therapy intervention group and the control group with 23 students as respondents in each group. After the cooperative game intervention was carried out for three weeks, statistical analysis with a paired t-test proved the effect of cooperative game therapy with a significant value (p = 0.000) and art therapy with a significant value (p = 0.001) while the Welch's ANOVA test showed a poshoc value (p = 0.032) Cooperative game play intervention was more effective than art therapy. These findings suggest that cooperative games are effective in reducing temper tantrum reactions. Therefore, nurses should introduce and recommend this approach to parents as a useful strategy for managing temper tantrum behavior.